2022
DOI: 10.1038/s41598-021-04249-w
|View full text |Cite
|
Sign up to set email alerts
|

Use of a language intervention to reduce vaccine hesitancy

Abstract: Vaccine hesitancy is a major global challenge facing COVID-19 immunization programs. Its main source is low public trust in the safety and effectiveness of the vaccine. In a preregistered experimental study, we investigated how using a foreign language when communicating COVID-19 vaccine information influences vaccine acceptance. Hong Kong Chinese residents (N = 611) received COVID-19 vaccine information either in their native Chinese or in English. English increased trust in the safety and effectiveness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
(35 reference statements)
1
14
0
3
Order By: Relevance
“…A second implication of the current research is that trust is key for crafting convincing vaccination messages 8,10 . However, our exploratory analyses indicate that different aspects of trust may be important for different demographics.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A second implication of the current research is that trust is key for crafting convincing vaccination messages 8,10 . However, our exploratory analyses indicate that different aspects of trust may be important for different demographics.…”
Section: Discussionmentioning
confidence: 93%
“…Western countries with sufficient public access to vaccines have insufficient vaccination rates 3 . A recent review of the psychological underpinnings of COVID-19 vaccine uptake has identified one key factor that promotes the decision to get vaccinated: Trust in the health authorities that recommend getting vaccinated 8 10 . This conclusion is also in line with past research on vaccine hesitancy that has identified confidence in vaccines and the system that delivers them is one of the keys to vaccine uptake 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Tankwanchi et al 18 believed that vaccine hesitancy among migrant communities is determined more by cultural barriers, religious beliefs, access to vaccines and trust rather than language per se. Interestingly, Geipel et al 19 found that Hong Kong Chinese patients (n=611) were more likely to accept COVID-19 immunisation when information was presented in English rather than their native Chinese and suggested that material in English somehow increased patient confidence in the safety and effectiveness of the vaccine; however, this may represent an underlying protest against the Chinese government by Hong Kongers rather than a preference for the English language! Abba-Aji et al 20 reviewed 31 studies on vaccine access among migrants and ethnic minorities and suggested that these groups may experience barriers related to trust, cultural issues and language but many of the studies reported here pertained more to issues of vaccine access rather than any reluctance to immunisation.…”
Section: Discussionmentioning
confidence: 99%
“…This may have both positive and negative consequences in the development field. In the health field (SDG 3-health and well-being) for instance, a study by Geipel et al [25] examined COVID-19 vaccine uptake among Hong-Kong participants. They found increased willingness to vaccinate when the advantages and disadvantages or risks of vaccination were described in a foreign language-English-rather than in their native language, Chinese.…”
Section: What We Know (Literature Review)mentioning
confidence: 99%
“…Research results suggest that people perceive novel technologies as less risky/more beneficial when they hear about their advantages and disadvantages than when they read about them. In other words, the modality in which information is conveyed-orally or via printed text-could also affects judgment, decision, and behaviour [25].…”
Section: What We Know (Literature Review)mentioning
confidence: 99%